THE ESSENCE OF HOSPITAL PEDAGOGY (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
Hospital pedagogy is a special pedagogical direction aimed at ensuring the continuation of the educational process of children who need long-term treatment. This direction involves the implementation of the educational and upbringing process taking into account the health and individual characteristics of children. The main goal of hospital pedagogy is to ensure the healthy development, social adaptation and non-lag in the educational process of children. The article analyzes the history of the development of hospital pedagogy, its main principles, problems encountered in the educational process and ways to overcome them. It also discusses the role of hospital pedagogy in society and its importance in the inclusive education system. Education for children who need long-term treatment is not only a process of acquiring knowledge, but also an important form of psychological and emotional support. This article is intended for educators, psychologists and health professionals and will help develop effective methods for working with sick children.